The Frontotemporal Dementias. - Landqvist, Maria (Psychiatric Clinics of North America, 2015)
Frontotemporal dementia (FTD) is a heterogeneous group of hereditary and sporadic neurodegenerative disorders affecting frontotemporal areas. FTD, a leading cause of young-onset dementia, is often initially mistaken for primary psychiatric disorders. Based on early and predominant symptoms, different clinical syndromes can be distinguished: the behavioral variant and 2 variants of progressive aphasia; semantic dementia and progressive nonfluent aphasia. Neuropathological classification is based on protein accumulation in the brain. Pathogenic mutations in different genes have been identified. Specific pharmacological treatment is the main research goal. Meanwhile the management must focus on early correct diagnosis, symptom alleviation, caregiver support and educational interventions.
The information about affiliations in this record was updated in December 2015. The record was previously connected to the following departments: Department of Psychogeriatrics (013304000)